Chemical and morphological studies on Zingiber zerumbet (Linn.) Smith and its proposed variety - Oliveros, Mildred Balbin 1943-
This study on the chemistry of the essential oils and morphology of Zingiber zerumbet (L.)Sm. and its proposed variety reveals significant differences between these 2 plants. Their main chemical differences are the following: dried rhizomes of Zingiber zerumbet (L.)Sm. yield an essential oil which is dextrorotatory, congealing at 3(degrees C), and having zerumbone as its main constituent. Rhizomes of the proposed variety yield an oil which is levorotatory, congealing at -27(degrees C), and having 4-terpinenol as its main constituent. The morphological differences between Zingiber zerumbet (L.) Smith and its proposed variety are the following: Zingiber zerumbet (L.)Sm. has ovate lanceolate leaves, about 5 times longer than wide; a prominent ligule, about 1.5 to 3.5 cm long; an inflorescence which is avoid to oblong with an obtuse apex; bracts which are green, pink-edged, abovate mucronate; pale-yellow rhizomes; and oil cells measuring from 30-90 u. The proposed variety, on the other hand, has oblong lanceolate leaves, about 8 times longer than wide; a small ligule, about 1 to 2 mm long; a cone-like inflorescence with an acute apex; obovate acute bracts which are brownish-purple and green-edged; yellow-orange rhizomes; and oil cells measuring from 50-136 u. On the strength of these chemical and morphological differences, it is proposed that the other plant be classified as a variety of Zingiber zerumbet (L.) Sm.